Clinical practice: Coeliac disease - Kneepkens, C. M. Frank (Springer-Verlag, 2012)
Coeliac disease (CD) is an immune-mediated systemic condition elicited by gluten and related prolamines in genetically predisposed individuals and characterised by gluten-induced symptoms and signs, specific antibodies, a specific human leukocyte antigen (HLA) type and enteropathy. The risk of coeliac disease is increased in first-degree relatives, certain syndromes including Down syndrome and autoimmune disorders. It is thought to occur in 1 in 100–200 individuals, but still only one in four cases is diagnosed. Small-bowel biopsy is no longer deemed necessary in a subgroup of patients, i.e. when all of the following are present: typical symptoms or signs, high titres of and transglutaminase antibodies, endomysial antibodies, and HLA-type DQ2 or DQ8. In all other cases, small-bowel biopsy remains mandatory for a correct diagnosis. Therapy consists of a strictly gluten-free diet. This should result in complete disappearance of symptoms and of serological markers. Adequate follow-up is considered essential. Conclusion: Although small-bowel biopsy may be omitted in a minority of patients, small-bowel biopsy is essential for a correct diagnosis of CD in all other cases. Diagnostic work-up should be completed before treatment with gluten-free diet instituted.